Acute Pulmonary Embolism Following Hemorrhagic Stroke - Gupta, Madhu; Prasad, Maheshwar; Lal, Achutanand; Mishra, Jeetendra; Ali, Imran; Bhatta, Parash; Khadka, Salina (Journal of National Heart and Lung Society Nepal, 2023)
Background: Venous thromboembolism results from extended immobilization following intracerebral hemorrhage. Massive pulmonary embolism in association with right heart failure is a life-threatening condition and requires treatment with anticoagulants or thrombolytic agents. There are no guidelines for treatment of pulmonary embolism with recent hemorrhagic stroke and these medicines are contraindicated, as they may induce farther hemorrhage.